GP12 Developmental dysplasia of hip – screening without radiographs; is it time?. (June 2019) - Jenkins, Elinor; Bell, Alison; Cassidy, Jane; Morris, Evangeline; Loughlin, Christopher O; Kelleher, John; Kelly, Paula
Abstract : Background: The optimum screening programme for developmental dysplasia of the hip remains elusive. Ireland has introduced a new national screening guideline based on selective USS. Aim: This study aims to determine the sensitivity of the new national guideline through a retrospective audit in one large teaching hospital. Methods: All infants referred for DDH imaging between 08/09/18 and 08/03/19 were included in the study. Infants with a normal USS (table 1 ) at 6 weeks were followed to radiograph at 6 months. A chart review of all infants with normal USS but abnormal or concerning radiograph was conducted to determine outcome. Results: 716 infants (17.3% of births) were referred for imaging based on clinical exam and current risk criteria. Of these, 655 infants (91.5%) had normal USS hips at 6 weeks. At 6 months 158 infants (24%) with normal USS had an abnormal or concerning x-ray pelvis. 131 (11.6%) were subject to surveillance but later discharged. 61 (9.3%) remain under surveillance, 13 (2%) required bracing. 74 (11%) DNA'd follow up appointments. To date none of the infants who had a normal USS have required surgery. Discussion and conclusion: A retrospective audit using USS with the addition of radiograph identified a potential 0 - 9.3% false negative rate and a sensitivity of 50%. While these figures are concerning, following the 61 infants currently under surveillance is important. Should no infant with normal USS require surgery clinicians may be more confident in the new national guideline.